Peran Generasi Z Dalam Paradigma Geopolitik Indonesia - Misbahul Munir; M. Wasith Achadi; Nurdhin Baroroh (Journal on Education, 2024)
In the era of Society 5.0 and Industrial Revolution 4.0, technological advances and globalization have triggered significant changes in various aspects of life, including geopolitics. Indonesia, with its position as the largest archipelagic country and abundant natural resources, has great potential for economic growth and geopolitical influence. Generation Z, born between 1997 and 2010, plays an important role in Indonesia's geopolitical paradigm. They are a digital native generation who grew up with technology and globalization, making them key actors in politics, society and the economy. This research aims to explore the role of Generation Z in overhauling Indonesia's geopolitical paradigm, using a literature study method that collects data from related journals and articles. The research results show that Generation Z utilizes digital technology to increase political participation, organize social movements, and promote citizen diplomacy. They are active in advocating global issues such as climate change, human rights, and gender equality, as well as encouraging sustainable business practices. The main findings of this research show that Generation Z in Indonesia is able to mobilize support and influence public policy through social media. Concrete examples include the #VoiceForClimate movement and protests against the Job Creation Law, which demonstrate their power in influencing public opinion and policy. In addition, their involvement in the digital economy and technological innovation creates new dynamics in the global economy, strengthening Indonesia's position on the international stage. The impact of this research confirms that Generation Z is a significant agent of change, bringing hope and inspiration for Indonesia's future. With an innovative, critical and progressive spirit, they are reshaping the national and global geopolitical landscape, ensuring their voices and values ​​are an integral part of the policy-making process.